Tissue factor in ulcerative colitis, with and without concomitant primary sclerosing cholangitis - Vessby, Johan; Lampinen, Maria; Åberg, Mikael; Rorsman, Fredrik; Siegbahn, Agneta; Wanders, Alkwin; Carlson, Marie (Upsala journal of medical sciences, 2019)
Background: Ulcerative colitis (UC) in patients with the severe disease primary sclerosing cholangitis (PSC) constitutes a distinct clinical phenotype (PSC-UC) with a high incidence of colorectal cancer. Today, PSC-UC diagnosis is built on clinical observations only. Tissue factor (TF) has a potential use in UC diagnostics, and also in colorectal cancer prognostication. Here we evaluate TF expression in an inflammatory bowel disease (IBD) cohort, with special focus on differences between UC and PSC-UC patients. Materials and methods: Colonic biopsies from UC (n = 23), PSC (n = 24), and healthy controls (n = 11) were stained for TF by immunohistochemistry. Mononuclear cell contribution to TF expression was verified using flow cytometry. Results: TF was distributed at three distinct colonic locations: in subepithelial pericryptal sheath cells, in mononuclear cells, and in the intestinal stroma. In contrast to UC-where inflammation was accompanied with TF up-regulation-PSC-UC activity remained low during inflammation. Stromal TF positivity was found exclusively in ongoing inflammation. Conclusion: Our study provides additional support for a divergent pathogenesis in PSC-UC, with an inflammatory environment that differs from classical UC. Stromal TF emerges as a new marker of colonic inflammation.